Pre-pregnancy body dissatisfaction and weight-related outcomes and behaviors during pregnancy. Issue 4 (1st July 2021) - Schlaff, Rebecca A.; Baruth, Meghan; Gherke, Jessika T.; Deere, Samantha J.
Abstract: To examine relationships among pre-pregnancy body dissatisfaction (BD) and gestational weight gain (GWG), and related attitudes/behaviors. Pre-pregnancy BD was self-reported in early pregnancy. Weight-related attitudes/behaviors were self-reported and physical activity was objectively measured during pregnancy. Overall, 92% of the women reported BD, with 69% desiring a smaller pre-pregnancy size than their actual pre-pregnancy size. Ideal pre-pregnancy weight was 20.7 ± 28 pounds less than self-reported pre-pregnancy weight. Only weight-control strategies used at 35 weeks were associated with BD ( p = 0.008). Pre-pregnancy BD may not predict risk for excess GWG and some weight-related issues during pregnancy.